Transformasi Tradisi Mbesur-mbesuri dalam Menyambut Kelahiran Anak pada Masyarakat Etnis Karo di Kecamatan Kutalimbaru, 2000–2020 - Akbar, Jamilun; Siregar, Yusra Dewi (Local History & Heritage, 2025)
The Mbesur-mbesuri tradition represents a vital element of the cultural heritage of the Karo ethnic group, historically performed as a ritual of reverence and protection for pregnant women entering their seventh month of gestation. Rooted in deeply held spiritual, symbolic, and communal values, the practice is believed to ensure the well-being of both mother and child. This study investigates how the Mbesur-mbesuri tradition has evolved within the Karo community in Kutalimbaru District between 2000 and 2020. It seeks to understand the extent to which modernity has influenced ritual practices and meanings. Using a qualitative descriptive approach within the framework of symbolic anthropology, data were gathered through literature review and in-depth interviews with local elders and custodians of the tradition. The study reveals that although the ritual has undergone noticeable simplification—such as the reduction of traditional offerings and ceremonial components—it has concurrently witnessed a renewed emphasis on its spiritual dimension. These changes reflect adaptive strategies that maintain cultural relevance while preserving essential values. The research concludes that Mbesur-mbesuri remains a potent symbol of identity and social cohesion, adapting to modern contexts without losing its foundational significance.